Natural Diversity in Flowering Responses of Arabidopsis thaliana Caused by Variation in a Tandem Gene Array - Rosloski, Sarah Marie (Genetics Society of America, 2010)
Tandemly arrayed genes that belong to gene families characterize genomes of many organisms. Gene duplication and subsequent relaxation of selection can lead to the establishment of paralogous cluster members that may evolve along different trajectories. Here, we report on the structural variation in MADS AFFECTING FLOWERING 2 (MAF2) gene, one member of the tandemly duplicated cluster of MADS-box-containing transcription factors in Arabidopsis thaliana. The altered gene structure at the MAF2 locus is present as a moderate-frequency polymorphism in Arabidopsis and leads to the extensive diversity in transcript patterns due to alternative splicing. Rearrangements at the MAF2 locus are associated with an early flowering phenotype in BC(5) lines. The lack of suppression of flowering time in a MAF2-insertion line expressing the MAF2-specific artificial miRNA suggests that these MAF2 variants are behaving as loss-of-function alleles. The variation in gene architecture is also associated with segregation distortion, which may have facilitated the spread and the establishment of the corresponding alleles throughout the Eurasian range of the A. thaliana population.